Then again, maybe I won't a novel - Blume, Judy (Dell Pub., 1971)
Unable to accept or explain his family's newly acquired wealth, his growing interest in sex, and a friend's shoplifting habit, a thirteen-year-old finds the pains in his stomach getting worse and worse.